2019
DOI: 10.1097/moh.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Emerging molecular mechanisms of vascular dementia

Abstract: Purpose of the review-Microvascular ischemic disease of the brain is a common cause of cognitive impairment and dementia, particularly in the context of preexisting cardiovascular risk factors and aging. This review summarizes our current understanding of the emerging molecular themes that underlie progressive and irreparable vascular pathology leading to neuronal tissue injury and dementia. Recent findings-Cardiometabolic risk factors including diabetes and hypertension are known to contribute to vascular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 62 publications
0
23
0
2
Order By: Relevance
“…Meanwhile, the further research (GO and pathway enrichment analysis) showed that the mechanism of MBHD to treat VD is mainly related to neuronal apoptosis, nitric oxide synthesis and metabolism, platelet activation, NF- κ B signaling pathway-mediated inflammation, oxidative stress, angiogenesis, etc. Current studies have shown that the pathogenesis of VD mainly includes (1) hypoperfusion and hypoxia caused by microvascular circulatory disorders, (2) increased blood-brain barrier permeability caused by endothelial dysfunction, (3) inflammation and oxidative stress damage the nutritional interaction between neurovascular unit cells, (4) ROS and inflammation inhibit the survival of neurons (neuron apoptosis), and (5) the destruction and demyelination of myelin tablets caused by the oxidative and proinflammatory environment caused by cerebral ischemia and hypoperfusion and the breakdown of the blood-brain barrier [ 1 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the further research (GO and pathway enrichment analysis) showed that the mechanism of MBHD to treat VD is mainly related to neuronal apoptosis, nitric oxide synthesis and metabolism, platelet activation, NF- κ B signaling pathway-mediated inflammation, oxidative stress, angiogenesis, etc. Current studies have shown that the pathogenesis of VD mainly includes (1) hypoperfusion and hypoxia caused by microvascular circulatory disorders, (2) increased blood-brain barrier permeability caused by endothelial dysfunction, (3) inflammation and oxidative stress damage the nutritional interaction between neurovascular unit cells, (4) ROS and inflammation inhibit the survival of neurons (neuron apoptosis), and (5) the destruction and demyelination of myelin tablets caused by the oxidative and proinflammatory environment caused by cerebral ischemia and hypoperfusion and the breakdown of the blood-brain barrier [ 1 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Efonidipine is a dual calcium channel blocker which inhibits both L-and T-type calcium channels. However, previous studies conducted on efonidipine indicate its crucial beneficial role in the management of cardiac hypertrophy, nephropathy, and hypertension in diabetic condition (Romay et al 2019;Sasaki et al 2009). Thus, the present study was designed to explore the effects of efonidipine in rat model of middle cerebral artery occlusion and to determine the mechanism of regulation of the TGF-β/SMAD2 signaling pathway after cerebral ischemia.…”
Section: Introductionmentioning
confidence: 98%
“…behind an increase in brain infarct volume in cerebral ischemia is increase in intracellular cytosolic calcium elevation which is resultant from the abrupt loss of cellular ATP from mitochondrial dysfunction, excessive depolarization from NMDA activation, and the increase of intracellular glutamate release due to astrocyte dysfunction (Romay et al 2019). Calcium homeostasis is crucial for cell survival and plays important role in apoptosis and necrosis (Pinton et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…VD is the second most common dementia disorder and comprises a heterogeneous group of conditions with a wide range of clinical and neuropathological presentations. Vascular pathology in the brain impairs superior cortical processes, including planning, reasoning, and memory as impaired cerebral blood flow leads to irreversible secondary focal neuronal injury (O’brien and Thomas, 2015 ; Romay et al, 2019 ). The prevalence of VD in China is 1.1% to 3.0%, and the annual incidence is 5–9/1,000 people (Chen et al, 2016 ; Yang et al, 2017 ).…”
Section: Ex-mirnas As Biomarkers In Other Dementia Disordersmentioning
confidence: 99%